Long Use Of Kb Pil Contraception With Hypertension Events In Kb Acceptor Community Health Center - Fitriani; Hamdana; Kasmira Ferly (Jurnal Life Birth, 2019)
Hypertension is a risk factor for cardiovascular disease caused by several factors. One factor can be caused due to oral contraception. Prolonged use of oral contraceptives can cause hypertension. Hypertension is one of the health problems suffered throughout the world including Indonesia. This study aims to analyze the Old Relationship of Contraceptive Pill Use and the Occurrence of Hypertension in Family Planning Acceptors in the Work Area of ​​Herlang Health Center in Bulukumba Regency in 2018.The design of this research was analytic observational with Cross Sectional design. The population in this study were all acceptors who used contraceptive pill as many as 250 respondents. The sample of this study were 71 people taken using the purposive sampling method. Data analysis used chi square test with p value (<0.05).The results showed that the duration of contraceptive use of birth control pills on old acceptors was 60 respondents with a percentage (84.5%), while not long ago there were 11 respondents with a percentage (15.5%). From the results of the incidence of hypertension, there are 45 respondents with hypertension percentage (63.4%) and those without hypertension are 26 respondents with a percentage (36.6%).The conclusion that there is a long-standing relationship between contraceptive use of birth control pills and the incidence of hypertension in family planning acceptors in the Work Area of ​​Herlang Public Health Center, Bulukumba Regency. It is recommended that the results of this study can be used as scientific reading material in the library and also used as reference material for students who are researching this type of problem.